The Effect of Digital Literacy and Social Media Utilization on MSME Performance in Klungkung Regency, Bali - Putra, Liangga; Muliadi, Dedi; Setyawan, Joko (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2026)
This study is grounded in the increasing importance of digital transformation among Micro and Small Enterprises (MSMEs) in Indonesia, particularly in tourism-based regions where competitiveness is closely tied to digital capability. Despite the rapid growth in digital adoption, many MSMEs still face challenges in effectively utilizing digital tools to enhance business performance, especially due to limited digital literacy and suboptimal use of social media. This research aims to examine the effect of digital literacy and social media utilization on MSME performance in Klungkung Regency, Bali. Using a quantitative explanatory approach, data were collected from 53 MSMEs across culinary, fashion, and craft sectors through purposive sampling. The data were analyzed using multiple linear regression with SPSS. The results indicate that digital literacy has a positive and significant effect on MSME performance, while social media utilization demonstrates a stronger and more dominant influence. Simultaneously, both variables significantly explain 59.2% of the variance in MSME performance. These findings highlight the critical role of digital capability, particularly social media optimization, in improving competitiveness and sustainability of MSMEs in tourism-based regions. This study contributes by providing empirical evidence in a relatively underexplored regional context and offers practical implications for policymakers in designing targeted digital empowerment programs.